2009
DOI: 10.1292/jvms.001459
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans, Cryptococcus neoformans or Aspergillus fumigatus Induces an Antifungal Activity in Mouse Serum, which is Different from Transferrin

Abstract: ABSTRACT. It has been reported that administration of Candida albicans into mouse induces an antifungal activity in serum, which has been identified as transferrin. In the present study, we show that not only C. albicans, but also other fungus such as Cryptococcus neoformans or Aspergillus fumigatus similarly can induce an antifungal activity in mouse serum. This antifungal activity was inhibited by the addition of ferrous ion, indicating that the growth inhibition of C. albicans was due to deficiency of ferro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Transferrin and lactoferrin are known to have an inhibitory effect on the growth of the pathogenic fungi A. fumigatus , C. albicans and C. neoformans (Sridhar et al, 2000 ; Ahluwalia et al, 2001 ; Lahoz et al, 2008 ; Almeida et al, 2009 ; Kornitzer, 2009 ; Okazaki et al, 2009 ). The mechanism of inhibition is probably due to iron sequestration by partially iron-loaded protein because additional studies have shown that these fungi can acquire iron from fully iron-loaded transferrin under specific conditions.…”
Section: Iron Acquisition From Transferrin Lactoferrin and Ferritinmentioning
confidence: 99%
“…Transferrin and lactoferrin are known to have an inhibitory effect on the growth of the pathogenic fungi A. fumigatus , C. albicans and C. neoformans (Sridhar et al, 2000 ; Ahluwalia et al, 2001 ; Lahoz et al, 2008 ; Almeida et al, 2009 ; Kornitzer, 2009 ; Okazaki et al, 2009 ). The mechanism of inhibition is probably due to iron sequestration by partially iron-loaded protein because additional studies have shown that these fungi can acquire iron from fully iron-loaded transferrin under specific conditions.…”
Section: Iron Acquisition From Transferrin Lactoferrin and Ferritinmentioning
confidence: 99%